A fluorine-doped lithium manganese iron phosphate positive electrode material and preparation method thereof

By doping fluorine into lithium manganese phosphate material and forming a SnO2/C cladding layer, the problems of poor circulation and rate performance of lithium manganese phosphate material are solved, and the material's conductivity and structural stability are improved.

CN119170787BActive Publication Date: 2025-02-11HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411645738.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The poor circulation and rate performance of lithium manganese iron phosphate material limits its practical application in lithium battery applications.

Method used

By doping fluorine in lithium manganese iron phosphate material, a fluorine-doped lithium manganese iron phosphate precursor is prepared by microwave-hydrothermal synthesis method, and a SnO2/C coating layer is formed on the surface of the material to improve the conductivity and structural stability of the material. sex.

Benefits of technology

The lithium ion diffusion kinetics are improved, the conductivity and cyclic performance of the cathode material are enhanced, and the rate performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium batteries, and discloses a fluorine-doped lithium iron manganese phosphate positive electrode material and a preparation method thereof. The fluorine-doped lithium iron manganese phosphate precursor is prepared by a microwave-hydrothermal synthesis method using hydrofluoric acid, manganese sulfate monohydrate, ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid as raw materials, and a coating layer is formed on the surface of the precursor using a chitosan gel doped with SnO2, and the fluorine-doped lithium iron manganese phosphate positive electrode material is obtained after calcination. The positive electrode material includes fluorine-doped lithium iron manganese phosphate particles and a SnO2 / C coating layer. The doping of fluorine promotes the diffusion of lithium ions in the positive electrode material, making the structure of the material more stable. SnO2 is doped in chitosan as a carbon source, which improves the conductivity of the positive electrode material. Based on the synergistic effect of the fluorine element and the metal ions of the coating layer, a uniform and tightly combined carbon coating layer is formed on the surface of the material. The fluorine-doped lithium iron manganese phosphate positive electrode material prepared by the present invention has excellent cycle performance and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a fluorine-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium iron phosphate is cheap, safe and environmentally friendly, and is suitable for automotive power batteries. However, due to its low energy density, lithium iron phosphate materials are difficult to meet the use requirements. Lithium manganese iron phosphate has a higher energy density than lithium iron phosphate, while taking into account the low cost and crystal structure stability of lithium iron phosphate, and has gradually become a substitute for lithium iron phosphate. However, the slow lithium ion diffusion kinetics and Mn 3+ The induced Jahn-Teller effect leads to poor cycle and rate performance of lithium manganese iron phosphate materials, limiting the practical application of lithium manganese iron phosphate. Summary of the invention

[0003] The object of the present invention is to provide a fluorine-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof, so as to improve the electrochemical performance of the lithium manganese iron phosphate positive electrode material.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] The present invention provides a fluorine-doped lithium iron manganese phosphate positive electrode material, wherein the fluorine-doped lithium iron manganese phosphate positive electrode material comprises fluorine-doped lithium iron manganese phosphate particles and a SnO2 / C coating layer;

[0006] The chemical formula of the fluorine-doped lithium manganese iron phosphate particles is: LiMn x Fe 1-x PO 4-y F y , where 0.5≤x≤0.8, 0.05≤y≤0.15;

[0007] The SnO2 / C coating layer is a carbon material doped with SnO2;

[0008] The carbon source of the carbon material is chitosan.

[0009] The present invention also provides a method for preparing the fluorine-doped lithium manganese iron phosphate positive electrode material, which is characterized by comprising the following steps:

[0010] Step 1, preparing raw materials: weighing hydrofluoric acid, manganese sulfate monohydrate, ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid according to the molar ratio of elements in the chemical formula of fluorine-doped lithium manganese iron phosphate particles;

[0011] Step 2, preparing a precursor: dissolving manganese sulfate monohydrate and ferrous sulfate heptahydrate in deionized water to form a metal salt solution, dissolving lithium hydroxide monohydrate in deionized water to form a lithium hydroxide solution, slowly adding phosphoric acid and hydrofluoric acid to the metal salt solution while stirring to form a mixed solution, stirring for 10-30 minutes, adding the lithium hydroxide solution dropwise to the mixed solution, adding ethylene glycol to the mixed solution and stirring for 10-30 minutes, placing the mixed solution in a microwave hydrothermal instrument for heating and reaction, centrifuging, washing and drying after the reaction is completed, and obtaining a fluorine-doped lithium iron manganese phosphate precursor;

[0012] Step 3. Prepare fluorine-doped lithium manganese iron phosphate positive electrode material: dissolve chitosan in acetic acid solution, add SnO2 and stir to obtain a SnO2 / chitosan mixed solution, add fluorine-doped lithium manganese iron phosphate precursor to the SnO2 / chitosan mixed solution, stir and mix under water bath heating conditions, vacuum dry and calcine under nitrogen atmosphere, and cool to room temperature to obtain a fluorine-doped lithium manganese iron phosphate positive electrode material.

[0013] Compared with the traditional hydrothermal synthesis method, microwaves can penetrate the reaction medium, directly act on the reacting molecules or atoms, stimulate the high-frequency vibration of polar molecules, and generate the heat required for the reaction through energy loss, thereby achieving overall rapid heating of the material, thereby shortening the reaction time, improving the reaction efficiency, and making the particle size of the material more uniform.

[0014] Furthermore, the concentration of the hydrofluoric acid is 30-40wt%, and the concentration of the phosphoric acid is 60-85wt%.

[0015] Furthermore, the concentration of manganese sulfate in the metal salt solution is 0.5-2 mol / L; the concentration of lithium hydroxide in the lithium hydroxide solution is 0.5-2 mol / L.

[0016] Furthermore, in the step 2, the volume ratio of the mixed solution to ethylene glycol is 1:1-3.

[0017] Furthermore, the temperature of the microwave hydrothermal instrument is set to 120-150° C., and the heating reaction time is 3-8 min.

[0018] Furthermore, the concentration of the acetic acid solution is 1-3wt%, and the chitosan is dissolved in the acetic acid solution at 1-3wt%.

[0019] Furthermore, the mass ratio of SnO2 to chitosan in the SnO2 / chitosan mixed solution is 1-2:5.

[0020] Furthermore, the mass ratio of the fluorine-doped lithium manganese iron phosphate precursor to chitosan added to the SnO2 / chitosan mixed solution is 1.1-1.6:1.

[0021] Furthermore, the water bath heating temperature is 80-90° C., and the mixture is stirred to form a viscous gel. The vacuum drying temperature is 110-125° C., the drying time is 12-24 hours, and the calcination temperature is 650-700° C., and the calcination time is 10-16 hours.

[0022] Beneficial effects of the present invention:

[0023] (1) In the present invention, a fluorine source is added to the raw material and a fluorine-doped lithium manganese iron phosphate precursor is prepared by a microwave-hydrothermal synthesis method. The fluorine doping promotes the lithium ion diffusion of the positive electrode material, making the structure of the material more stable and improving the conductivity of the positive electrode material.

[0024] (2) Chitosan, which is used as a carbon source, is doped with SnO2 to improve the conductivity of the positive electrode material. At the same time, during the calcination process, part of the tin oxide is reduced to metallic tin due to the carbon thermal reduction reaction, which can further improve the conductivity of the coating layer.

[0025] (3) Based on the coordination effect between the metal ions (tin ions) in the coating layer and the exposed fluorine atoms in the precursor, the chitosan gel can form a uniform and tightly bound carbon coating layer on the surface of the material, so that the positive electrode material obtained by the present invention has excellent cycle performance and rate performance. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] Step 1: Prepare raw materials: According to the chemical formula of fluorine-doped lithium manganese iron phosphate particles (LiMn 0.5 Fe 0.5 PO 3.95 F 0.05 ) Weigh hydrofluoric acid (concentration of 40wt%), manganese sulfate monohydrate, ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid (concentration of 85wt%);

[0029] Step 2, prepare the precursor: dissolve manganese sulfate monohydrate and ferrous sulfate heptahydrate in deionized water to form a metal salt solution, the concentration of manganese sulfate is 1 mol / L, and lithium hydroxide monohydrate is dissolved in deionized water to form a lithium hydroxide solution, and the concentration of lithium hydroxide is 0.5 mol / L. Phosphoric acid and hydrofluoric acid are slowly added to the metal salt solution while stirring to form a mixed solution, and the lithium hydroxide solution is added dropwise to the mixed solution after stirring for 10 minutes, and ethylene glycol is added to the mixed solution at a volume ratio of 1:1, and stirred for 10 minutes, and placed in a microwave hydrothermal instrument for heating reaction, and the heating temperature is set to 150°C. The reaction ends after the heating reaction for 5 minutes, and the product is centrifuged and the precipitate is washed with deionized water, and the fluorine-doped lithium iron manganese phosphate precursor is obtained after drying;

[0030] Step 3, preparation of fluorine-doped lithium manganese iron phosphate positive electrode material: chitosan is dissolved in an acetic acid solution with a concentration of 1wt% at a concentration of 2wt%, SnO2 is added at a mass ratio of SnO2 to chitosan of 1:5, and the mixture is stirred to obtain a SnO2 / chitosan mixed solution, and fluorine-doped lithium manganese iron phosphate precursor is added to the SnO2 / chitosan mixed solution at a mass ratio of fluorine-doped lithium manganese iron phosphate precursor to chitosan of 1.1:1, and the mixture is stirred and mixed under heating conditions at 90°C in a water bath until a viscous gel is formed, and the mixture is vacuum dried at 110°C for 24h, calcined at 650°C for 10h under a nitrogen atmosphere, and cooled to room temperature to obtain a fluorine-doped lithium manganese iron phosphate positive electrode material.

[0031] Example 2

[0032] The difference from Example 1 is that the mass ratio of SnO2 to chitosan is adjusted to 1.5:5, and the other steps and conditions are the same as Example 1.

[0033] Example 3

[0034] The difference from Example 1 is that the mass ratio of SnO2 to chitosan is adjusted to 2:5, and the other steps and conditions are the same as Example 1.

[0035] Example 4

[0036] The difference from Example 1 is that the mass ratio of fluorine-doped lithium manganese iron phosphate precursor to chitosan is adjusted to 1.3:1, and the other steps and conditions are the same as Example 1.

[0037] Example 5

[0038] The difference from Example 1 is that the mass ratio of fluorine-doped lithium manganese iron phosphate precursor to chitosan is adjusted to 1.6:1, and the other steps and conditions are the same as Example 1.

[0039] Example 6

[0040] The difference from Example 1 is that: according to the chemical formula of fluorine-doped lithium manganese iron phosphate particles (LiMn0.7 Fe 0.3 PO 3.9 F 0.1 ) are weighed, and the other steps and conditions are the same as those in Example 1.

[0041] Example 7

[0042] The difference from Example 1 is that: according to the chemical formula of fluorine-doped lithium manganese iron phosphate particles (LiMn 0.8 Fe 0.2 PO 3.85 F 0.15 ) are weighed, and the other steps and conditions are the same as those in Example 1.

[0043] Comparative Example 1

[0044] Compared with Example 1, the difference of this comparative example is that the positive electrode material is not doped with fluorine element, and according to the chemical formula of lithium manganese iron phosphate particles (LiMn 0.5 Fe 0.5 PO4) to weigh the raw materials. The specific steps are as follows:

[0045] Step 1: Prepare raw materials: According to the chemical formula of lithium manganese iron phosphate particles (LiMn 0.5 Fe 0.5 PO4) weigh manganese sulfate monohydrate, ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid (concentration 85wt%);

[0046] Step 2, prepare the precursor: dissolve manganese sulfate monohydrate and ferrous sulfate heptahydrate in deionized water to form a metal salt solution, the concentration of manganese sulfate is 1 mol / L, and lithium hydroxide monohydrate is dissolved in deionized water to form a lithium hydroxide solution, and the concentration of lithium hydroxide is 0.5 mol / L. Phosphoric acid is slowly added to the metal salt solution while stirring to form a mixed solution, and the lithium hydroxide solution is added dropwise to the mixed solution after stirring for 10 minutes, and ethylene glycol is added to the mixed solution at a volume ratio of 1:1, and stirred for 10 minutes, and placed in a microwave hydrothermal instrument for heating reaction, and the heating temperature is set to 150°C. The reaction ends after the heating reaction for 5 minutes, and the product is centrifuged and the precipitate is washed with deionized water, and dried to obtain a lithium iron manganese phosphate precursor;

[0047] Step 3, prepare lithium iron manganese phosphate positive electrode material: dissolve chitosan at a concentration of 2wt% in an acetic acid solution with a concentration of 1wt%, add SnO2 at a mass ratio of SnO2 to chitosan of 1:5, stir and mix to obtain a SnO2 / chitosan mixed solution, add lithium iron manganese phosphate precursor to the SnO2 / chitosan mixed solution at a mass ratio of lithium iron manganese phosphate precursor to chitosan of 1.1:1, stir and mix under heating conditions at 90°C in a water bath until a viscous gel is formed, vacuum dry at 110°C for 24h, calcine at 650°C for 10h under a nitrogen atmosphere, and cool to room temperature to obtain a lithium iron manganese phosphate positive electrode material.

[0048] Comparative Example 2

[0049] Compared with Example 1, the difference of this comparative example is that the coating layer material is not doped with SnO2, and the specific steps are as follows:

[0050] Step 1: Prepare raw materials: According to the chemical formula of fluorine-doped lithium manganese iron phosphate particles (LiMn 0.5 Fe 0.5 PO 3.95 F 0.05 ) Weigh hydrofluoric acid (concentration of 40wt%), manganese sulfate monohydrate, ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid (concentration of 85wt%);

[0051] Step 2, prepare the precursor: dissolve manganese sulfate monohydrate and ferrous sulfate heptahydrate in deionized water to form a metal salt solution, the concentration of manganese sulfate is 1 mol / L, and lithium hydroxide monohydrate is dissolved in deionized water to form a lithium hydroxide solution, and the concentration of lithium hydroxide is 0.5 mol / L. Phosphoric acid and hydrofluoric acid are slowly added to the metal salt solution while stirring to form a mixed solution, and the lithium hydroxide solution is added dropwise to the mixed solution after stirring for 10 minutes, and ethylene glycol is added to the mixed solution at a volume ratio of 1:1, and stirred for 10 minutes, and placed in a microwave hydrothermal instrument for heating reaction, and the heating temperature is set to 150°C. The reaction ends after the heating reaction for 5 minutes, and the product is centrifuged and the precipitate is washed with deionized water, and the fluorine-doped lithium iron manganese phosphate precursor is obtained after drying;

[0052] Step 3, preparation of fluorine-doped lithium manganese iron phosphate positive electrode material: chitosan was dissolved in 1wt% acetic acid solution at a concentration of 2wt% to obtain a chitosan mixed solution, and the fluorine-doped lithium manganese iron phosphate precursor was added to the chitosan mixed solution at a mass ratio of 1.1:1 between the fluorine-doped lithium manganese iron phosphate precursor and chitosan, and the mixture was stirred and mixed under heating conditions at 90°C in a water bath to form a viscous gel, vacuum dried at 110°C for 24h, calcined at 650°C for 10h under a nitrogen atmosphere, and cooled to room temperature to obtain a fluorine-doped lithium manganese iron phosphate positive electrode material.

[0053] Comparative Example 3

[0054] Compared with Example 1, the difference of this comparative example is that the positive electrode material is not doped with fluorine element and the coating layer material is not doped with SnO2. The specific steps are as follows:

[0055] Step 1: Prepare raw materials: According to the chemical formula of lithium manganese iron phosphate particles (LiMn 0.5 Fe 0.5 PO4) weigh manganese sulfate monohydrate, ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid (concentration 85wt%);

[0056] Step 2, prepare the precursor: dissolve manganese sulfate monohydrate and ferrous sulfate heptahydrate in deionized water to form a metal salt solution, the concentration of manganese sulfate is 1 mol / L, and lithium hydroxide monohydrate is dissolved in deionized water to form a lithium hydroxide solution, and the concentration of lithium hydroxide is 0.5 mol / L. Phosphoric acid is slowly added to the metal salt solution while stirring to form a mixed solution, and the lithium hydroxide solution is added dropwise to the mixed solution after stirring for 10 minutes, and ethylene glycol is added to the mixed solution at a volume ratio of 1:1, and stirred for 10 minutes, and placed in a microwave hydrothermal instrument for heating reaction, and the heating temperature is set to 150°C. The reaction ends after the heating reaction for 5 minutes, and the product is centrifuged and the precipitate is washed with deionized water, and dried to obtain a lithium iron manganese phosphate precursor;

[0057] Step 3, prepare lithium iron manganese phosphate positive electrode material: dissolve chitosan at a concentration of 2wt% in an acetic acid solution with a concentration of 1wt% to obtain a chitosan mixed solution, add the lithium iron manganese phosphate precursor to the chitosan mixed solution at a mass ratio of 1.1:1 between the lithium iron manganese phosphate precursor and chitosan, stir and mix under heating conditions at 90°C in a water bath to form a viscous gel, vacuum dry at 110°C for 24h, calcine at 650°C under a nitrogen atmosphere for 10h, and cool to room temperature to obtain the lithium iron manganese phosphate positive electrode material.

[0058] The performance of the positive electrode materials prepared in Example 1 to Example 7 and Comparative Example 1 to Comparative Example 3 was tested. The results are shown in Table 1. The detection reference is T / CIAPS0029-2023 "Lithium manganese iron phosphate positive electrode material for lithium ion batteries" standard.

[0059]

[0060] As can be seen from Table 1, in Examples 1 to 3, the electrochemical performance of the positive electrode material is significantly improved by increasing the proportion of tin oxide in the coating layer. In Examples 4 and 5, the ratio of the precursor and chitosan in Example 1 is adjusted. When the proportion of the precursor increases, the carbon content decreases, resulting in a decrease in conductivity and a decrease in the discharge specific capacity. Among them, although the carbon content of Example 4 is reduced, the proportion of the precursor as an active material increases, which slightly increases the specific capacity of the positive electrode material compared with Example 1. Since the positive electrode materials of Examples 1, 6 and 7 are prepared according to different molar ratios of elements, their electrochemical properties will change. Due to excessive doping of fluorine in Example 7, its rate performance is significantly reduced. Combining Comparative Examples 1, 2 and 3 with Example 1, it can be seen that the electrochemical performance of the positive electrode material doped with fluorine and containing tin oxide in the coating layer in Example 1 is significantly better than that of the comparative example.

[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fluorine-doped lithium manganese iron phosphate positive electrode material, characterized in that: The fluorine-doped lithium manganese iron phosphate positive electrode material comprises fluorine-doped lithium manganese iron phosphate particles and a SnO2 / C coating layer; The chemical formula of the fluorine-doped lithium manganese iron phosphate particles is: LiMn x Fe 1-x PO 4-y F y , where 0.5≤x≤0.8, 0.05≤y≤0.15; The SnO2 / C coating layer is a carbon material doped with SnO2; The carbon source of the carbon material is chitosan; The method for preparing the fluorine-doped lithium manganese iron phosphate positive electrode material comprises the following steps: Step 1, preparing raw materials: weighing hydrofluoric acid, manganese sulfate monohydrate, ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid according to the molar ratio of elements in the chemical formula of fluorine-doped lithium manganese iron phosphate particles; Step 2, preparing a precursor: dissolving manganese sulfate monohydrate and ferrous sulfate heptahydrate in deionized water to form a metal salt solution, dissolving lithium hydroxide monohydrate in deionized water to form a lithium hydroxide solution, slowly adding phosphoric acid and hydrofluoric acid to the metal salt solution while stirring to form a mixed solution, stirring for 10-30 minutes, adding the lithium hydroxide solution dropwise to the mixed solution, adding ethylene glycol to the mixed solution and stirring for 10-30 minutes, placing the mixed solution in a microwave hydrothermal instrument for heating and reaction, centrifuging, washing and drying after the reaction is completed, and obtaining a fluorine-doped lithium iron manganese phosphate precursor; Step 3. Prepare fluorine-doped lithium manganese iron phosphate positive electrode material: dissolve chitosan in acetic acid solution, add SnO2 and stir to obtain a SnO2 / chitosan mixed solution, add fluorine-doped lithium manganese iron phosphate precursor to the SnO2 / chitosan mixed solution, stir and mix under water bath heating conditions, vacuum dry and calcine under nitrogen atmosphere, and cool to room temperature to obtain a fluorine-doped lithium manganese iron phosphate positive electrode material.

2. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The concentration of the hydrofluoric acid is 30-40wt%, and the concentration of the phosphoric acid is 60-85wt%.

3. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The concentration of manganese sulfate in the metal salt solution is 0.5-2 mol / L; the concentration of lithium hydroxide in the lithium hydroxide solution is 0.5-2 mol / L.

4. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The volume ratio of the mixed solution to ethylene glycol in step 2 is 1:1-3.

5. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The temperature of the microwave hydrothermal instrument is set to 120-150° C., and the heating reaction time is 3-8 min.

6. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The concentration of the acetic acid solution is 1-3wt%, and the chitosan is dissolved in the acetic acid solution at 1-3wt%.

7. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The mass ratio of SnO2 to chitosan in the SnO2 / chitosan mixed solution is 1-2:

5.

8. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The mass ratio of the fluorine-doped lithium manganese iron phosphate precursor to chitosan added to the SnO2 / chitosan mixed solution is 1.1-1.6:

1.

9. The fluorine-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The water bath heating temperature is 80-90° C., and the mixture is stirred to form a viscous gel. The vacuum drying temperature is 110-125° C., the drying time is 12-24 hours, and the calcination temperature is 650-700° C., and the calcination time is 10-16 hours.

Citation Information

Patent Citations

  • Preparation method of fluorine ion doped and lithium fluoride coated lithium iron phosphate positive electrode material

    CN109904423A

  • Preparation method and application of metal-doped carbon in-situ coated lithium iron phosphate electrode material

    CN114551823A